Plant growth-promoting rhizobacterial inoculation to improve growth, yield, and grain nutrient uptake of teff varieties - Tsegaye, Zerihun; Alemu, Tesfaye; Desta, Feleke Adey; Assefa, Fassil (Frontiers in Microbiology, 2022)
Inoculation of PGPR improves growth, yield and plant nutrient uptake as well as improve rhizosphere fertility without harming the environment and human health. The present study aimed to examine the effect of either individual or consortium of PGP bacterial inoculation on growth, yield, and grain nutrient uptake of teff varieties. Three potential PGPR strains (Pseudomonas fluorescens biotype G, Enterobacter cloacae ss disolvens, and Serratia marcescens ss marcescen) were used for this study. Field evaluation was carried out in RCBD with 5 treatments. Highly significant (P< 0.001) differences were observed among treatments for Plant height (PH), Panicle length (PL), number of the total spike (NTS), shoot dry weight (SDW), Grain yield (GY), and Straw yield (SY). There was also teff variety significantly (P< 0.01) affects PL, SDW, and SY. However, the interaction effect of the two factors (treatment*variety) did not significantly influence teff agronomic traits and grain nutrient uptake. The highest PH (133.5cm), PL (53.2), NTS (30.9), SDW (18.1 t ha-1), SY (10.7t/h), and GY (2.7 t ha-1) were observed on Dukem variety (Dz-01-974) inoculated with PGPR consortium. The magnitude of increase in grain yield per hectare was 45% over control. Inoculation of consortium of PGPR showed better performance in promoting plant growth, yield, and grain nutrient uptake of teff varieties compared to the control and could be used as inoculants to enhance teff production and productivity.